The osmolyte type affects cartilage associated pathologic marker expression during in vitro mesenchymal stem cell chondrogenesis under hypertonic conditions - Ahmadyan, Sorour; Kabiri, Mahboubeh; Tasharofi, Noushin; Hosseinzadeh, Simzar; Kehtari, Mousa; Hajari Zadeh, Athena; Soleimani, Masoud; Farazmand, Ali; Hanaee-Ahvaz, Hana (Cellular and Molecular Biology, 2018)
Stem cells' fate during in vitro differentiation is influenced by biophysicochemical cues. Osmotic stress has proved to enhance chondrocyte marker expression, however its potent negative impacts had never been surveyed. We questioned whether specific osmotic conditions, regarding the osmolyte agent, could benefit chondrogenesis while dampening undesired concomitant hypertrophy and inflammatory responses. To examine the potential side effects of hypertonicity, we assessed cell proliferation as well as chondrogenic and hypertrophic marker expression of human Adipose Derived-MSC after a two week induction in chondrogenic media with either NaCl or Sorbitol, as the osmolyte agent to reach a +100 mOsm hypertonic condition. Calcium deposition and TNF-Î± secretion as markers associated with hypertrophy and inflammation were then assayed. While both hyperosmotic conditions upregulated chondrogenic markers, sorbitol had a nearly three times higher chondro-promotive effect and a lesser hypertrophic effect compared to NaCl. Also, a significantly lesser calcium deposition was observed in sorbitol hypertonic group. NaCl showed an anti-proinflammatory effect while sorbitol had no effect on inflammatory markers. The ossification potential and cartilage associated pathologic markers were affected differentially by the type of the osmolyte. Thus, a vigilant application of the osmotic agent is inevitable in order to avoid or reduce undesired hypertrophic and inflammatory phenotype acquisition by MSC during chondrogenic differentiation. Our findings are a step towards developing a more reliable chondrogenic regimen using external hypertonic cues for MSC chondrogenesis with potential applications in chondral lesions cell therapy.